PENGARUH FREE CASH FLOW DAN RETURN ON ASSET TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN LQ45 - Herlina Herlina; Edi Sutanto; Shinta Cahyani (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2021)
This study examines the effect of free cash flow and return on assets on dividend policy in LQ45 companies in 2013-2017. This goal is to find out whether there is an influence between free cash flow and return on assets on dividend policy. The analysis technique used is multiple linear regression analysis.Based on data from the t test that X1 from the regression results shows t count of 2.135 and the value of t table 2.01174 the significance level is 0.038. This result shows the value of t count (2.135) t table value (2.01174) with a significance value of 0.038 which means it is smaller than 0.05, it can be concluded that partially free cash flow has a positive effect on dividend policy in LQ45 companies in 2013-2017. Then H0 is rejected and H1 is accepted.And X2 from the regression results show t count of 1.556 and t table value of 2.01174 significance level of 0.126. These results indicate the value of t count (1.556) t table value (2.01174) with a significance value of 0.126 which means greater than 0.05 partial return on assets does not have a positive effect on dividend policy in LQ45 companies in 2013-2017. Then H0 is accepted and H2 is rejected.Taken together, the f test is 42,047 and the F value of table 3.19 is a significance level of 0,000. This result shows the value of F count (42,047) the value of F table (3.19) with a significance value of 0,000 which means it is smaller than the significance value of 0.05, it can be concluded simultaneously free cash flow and return on assets have a positive and significant effect on dividend policy. Then H0 is rejected and H3 is accepted.The results of this study indicate that free cash flow has a positive effect on dividend policy, and return on assets does not affect dividend policy.